Estudio de mejora para la implementación del sistema HACCP en la línea de hamburguesas veganas de la empresa DELLANATURA S.A.C. - Contreras Malásquez, Julio Miguel (2020)
This work was developed in the company DELLANATURA S.A.C. which, given the slowdown in the growth of its annual sales, opted to improve its value offer, by certifying the HACCP system in the line of vegan burgers, and thus attracting new customers in the HORECA channel, which is composed by businesses such as hotels, restaurants and caterings. After performing an evaluation to the food safety management system, which includes the prerequisite programs (BPM and POES) and making the respective updates, the methodology of the 12 steps for the implementation of the HACCP system was executed, through which two critical control points (cooking and freezing stages) were identified and their correspondent critical limits were established (LC cooking: T> 70 ° C, LC freezing: T <-20 ° C). The PCC monitoring system and the corrective actions to be taken, in case the required values were not reached, were established. The verification procedures and the validation of the system to be implemented were developed as well. Finally, three scenarios were proposed based on the growth in profit from sales in the HORECA channel for a period of three years and using a 15% annual rate, obtaining a benefit / cost ratio greater than one in each case (B / C optimistic = 1.36; B / C moderate = 1.20 and B / C pessimistic = 1.11).